The Effect of Ice Breaking on Student Focus in Physical Education, Health, and Sports (PJOK) Lessons at Mutiara Bunda 2 Junior High School in Sidoarjo - Randi Esrayanto Benu; Luqmanul Hakim (Journal of Comprehensive Science, 2026)
This study aims to determine the effect of implementing Ice Breaking strategies on improving students' learning focus in Pendidikan Jasmani, Olahraga, dan Kesehatan (PJOK) subjects at SMP Mutiara Bunda 2 Sidoarjo. The research is motivated by the phenomenon of boredom and low student concentration during the learning process, which often hinders optimal material absorption. The research method is a quantitative quasi-experimental approach with a pretest-posttest control group design. The research population includes all 7th-grade students at SMP Mutiara Bunda 2 Sidoarjo, with a sample of 30 students selected through purposive sampling. The sample was divided into two groups: an experimental group that received Ice Breaking treatment and a control group using conventional learning methods. Data collection instruments included learning outcomes tests (pretest and posttest questions) and student learning focus observation sheets. Data analysis using the Independent Samples t-Test yielded a significant value (2-tailed p=0.000 <0.05 p=0.000<0.05). The average posttest score for the experimental group (79.33) was significantly higher than that of the control group (46.00). Based on these results, it can be concluded that applying Ice Breaking has a positive and significant influence on increasing students' learning focus in PJOK lessons. This study suggests that PJOK teachers integrate various ice-breaking activities to create a more interactive and conducive learning atmosphere.